Paved Over: At the Intersection of Urban Mobility, Class Politics, and the Limits of Power in Mexico City, 1920s-1960s - Michael K. Bess (My University, 2023)
The mid-twentieth-century history of urban modernization and mobility in Mexico City was intertwined with political violence. It ranged from the forceful clearing of a working-class community to make way for a stadium parking lot to the “slow violence” of denying people access to trolleys to transport their goods or weaponizing transit policy to reward friends and punish rivals. This article shows how these activities reflected the increasingly violent decisions of an indifferent national and local elite rooted in Mexico City’s political reorganization, which created a powerful, centralized, and unelected bureaucracy: the Department of the Federal District. Public officials, engineers, business leaders, everyday citizens, and newspapers contested issues related to urban mobility. These engagements shaped how people lived and moved in the district and were affected by class politics. They also provoked new configurations for democratic intervention that led people to organize, protest, and resist state power in Mexico City.